2013
DOI: 10.1007/s00125-013-3131-6
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 in mouse pancreatic beta cells plays a crucial role in glucose homeostasis by regulating beta cell mass

Abstract: TCF7L2 expressed in the pancreatic beta cells plays a crucial role in glucose metabolism through regulation of the beta cell mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 49 publications
2
67
2
Order By: Relevance
“…Surprisingly, they reported no impaired effects on b-cell function in a b-cellspecific Tcf7l2 knockout mouse (23). This finding is in sharp contrast with previous reports showing reduced b-cell mass, a perturbed incretin response and GSIS with reduced insulin expression (24,27). Although there are no apparent explanations for these discrepant results they could reflect the application of B-cell-specific versus whole-islet knockdown strategies, as TCF7L2 is also expressed in a-cells (55), or a difference between inducible versus congenital knockdown of TCF7L2, as Wnt signaling is important for pancreas development (62).…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Surprisingly, they reported no impaired effects on b-cell function in a b-cellspecific Tcf7l2 knockout mouse (23). This finding is in sharp contrast with previous reports showing reduced b-cell mass, a perturbed incretin response and GSIS with reduced insulin expression (24,27). Although there are no apparent explanations for these discrepant results they could reflect the application of B-cell-specific versus whole-islet knockdown strategies, as TCF7L2 is also expressed in a-cells (55), or a difference between inducible versus congenital knockdown of TCF7L2, as Wnt signaling is important for pancreas development (62).…”
contrasting
confidence: 56%
“…In support of a primary effect in pancreatic islets, the risk T-allele carriers show higher degree of open chromatin in pancreatic islets, but not in other tissues (22). Several mouse models of Tcf7l2 have been investigated (23)(24)(25)(26)(27)(28), but the diabetic phenotype has not been replicated in all studies. Experiments in rodent islets where TCF7L2 activity has been disrupted have usually demonstrated impaired GSIS (11,29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the TCF7L2 gene is involved in modifying the expression of insulin and glucagon protein through Wnt signaling. A previous study has demonstrated a significant association between high expression of TCF7L2 in pancreatic beta cells and glucose metabolism (Takamoto et al, 2014). Zhou et al (2014) reported that the T allele of rs7903146, associated with diabetes risk, correlates with increased TCF7L2 expression and reduced insulin levels and secretion, thus the affected protein may regulate insulin production and the pathogenesis of type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 98%
“…For example, TCF7L2 had no known role in T2D when intronic SNPs were first found to be associated with this disease. Subsequent expression and functional studies have now identified a key role for this gene in pancreatic beta-cell function [58][59].…”
Section: Association Does Not Imply Causalitymentioning
confidence: 99%